2020
DOI: 10.3390/jcm9103241
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Humoral Immune Responses against Toxin A and B of Clostridium difficile is Associated with a Milder Disease Manifestation

Abstract: The role of the humoral immune response to Clostridium difficile in modulating the severity of C. difficile infection (CDI) is unclear. We compared the levels of serum immunoglobulin G (IgG) and immunoglobulin A (IgA) against toxin A (TcdA) and toxin B (TcdB) of C. difficile between CDI and control patients and according to disease severity. The levels of IgG and IgA antibodies against TcdA and TcdB were measured in sera from patients with CDI (n = 50; 19 had severe CDI) and control patients (n = 52), using EL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…The role of the humoral immune response to Clostridium difficile in modulating the severity of C. difficile infection remains unclear. In this Special Issue, Na’amnih W. et al found higher IgG levels against TcdA and TcdB in patients with mild versus severe CDI [ 8 ]. These preliminary findings provide a basis for future large-scale studies and support the development and evaluation of active and passive immunotherapies for C. difficile infection management.…”
mentioning
confidence: 99%
“…The role of the humoral immune response to Clostridium difficile in modulating the severity of C. difficile infection remains unclear. In this Special Issue, Na’amnih W. et al found higher IgG levels against TcdA and TcdB in patients with mild versus severe CDI [ 8 ]. These preliminary findings provide a basis for future large-scale studies and support the development and evaluation of active and passive immunotherapies for C. difficile infection management.…”
mentioning
confidence: 99%